TBK1 Mutation Spectrum in an Extended European Patient Cohort with Frontotemporal Dementia and Amyotrophic Lateral Sclerosis - van der Zee, Julie; Gijselinck, Ilse; Van Mossevelde, Sara; Perrone, Federica; Dillen, Lubina; Heeman, Bavo; Bäumer, Veerle; Engelborghs, Sebastiaan; De Bleecker, Jan; Baets, Jonathan; Gelpi, Ellen; Rojas-García, Ricardo; et al. (Human mutation, 2017)
We investigated the mutation spectrum of the TANK-Binding Kinase 1 (TBK1) gene and its associated phenotypic spectrum by exonic resequencing of TBK1 in a cohort of 2,538 patients with frontotemporal dementia (FTD), amyotrophic lateral sclerosis (ALS), or FTD plus ALS, ascertained within the European Early-Onset Dementia Consortium. We assessed pathogenicity of predicted protein-truncating mutations by measuring loss of RNA expression. Functional effect of in-frame amino acid deletions and missense mutations was further explored in vivo on protein level and in vitro by an NFκB-induced luciferase reporter assay and measuring phosphorylated TBK1. The protein-truncating mutations led to the loss of transcript through nonsense-mediated mRNA decay. For the in-frame amino acid deletions, we demonstrated loss of TBK1 or phosphorylated TBK1 protein. An important fraction of the missense mutations compromised NFκB activation indicating that at least some functions of TBK1 are lost. Although missense mutations were also present in controls, over three times more mutations affecting TBK1 functioning were found in the mutation fraction observed in patients only, suggesting high-risk alleles (P = 0.03). Total mutation frequency for confirmed TBK1 LoF mutations in the European cohort was 0.7%, with frequencies in the clinical subgroups of 0.4% in FTD, 1.3% in ALS, and 3.6% in FTD-ALS.
Keywords: mutace; aktivace enzymů; heterozygot; sekvenční delece; frontotemporální demence; Female; Phenotype; Enzyme Activation; ženské pohlaví; substituce aminokyselin; lidé; Heterozygote; Amino Acid Substitution; Protein Serine-Threonine Kinases; Mutation; studie případů a kontrol; amyotrofická laterální skleróza; kohortové studie; Middle Aged; Cohort Studies; genetické asociační studie; Male; Case-Control Studies; Aged; Frontotemporal Dementia; Amyotrophic Lateral Sclerosis; alely; Alleles; lidé středního věku; senioři; mužské pohlaví; NF-kappa B; fenotyp; White People; Sequence Deletion; běloši; protein-serin-threoninkinasy; Genetic Association Studies; Humans